Recurrence of idiopathic acute pancreatitis after cholecystectomy: systematic review and meta‐analysis. Issue 3 (25th December 2019) - Umans, D. S.; Hallensleben, N. D.; Verdonk, R. C.; Bouwense, S. A. W.; Fockens, P.; van Santvoort, H. C.; Voermans, R. P.; Besselink, M. G.; Bruno, M. J.; van Hooft, J. E.; ,
Abstract : Background: Occult biliary disease has been suggested as a frequent underlying cause of idiopathic acute pancreatitis (IAP). Cholecystectomy has been proposed as a strategy to prevent recurrent IAP. The aim of this systematic review was to determine the efficacy of cholecystectomy in reducing the risk of recurrent IAP. Methods: PubMed, Embase and Cochrane Library databases were searched systematically for studies including patients with IAP treated by cholecystectomy, with data on recurrence of pancreatitis. Studies published before 1980 or including chronic pancreatitis and case reports were excluded. The primary outcome was recurrence rate. Quality was assessed using the Newcastle–Ottawa Scale. Meta‐analyses were undertaken to calculate risk ratios using a random‐effects model with the inverse‐variance method. Results: Overall, ten studies were included, of which nine were used in pooled analyses. The study population consisted of 524 patients with 126 cholecystectomies. Of these 524 patients, 154 (29·4 (95 per cent c.i. 25·5 to 33·3) per cent) had recurrent disease. The recurrence rate was significantly lower after cholecystectomy than after conservative management (14 of 126 (11·1 per cent) versus 140 of 398 (35·2 per cent); risk ratio 0·44, 95 per cent c.i. 0·27 to 0·71). Even in patients in whom IAP was diagnosed after more extensive diagnostic testing, including endoscopic ultrasonography or magnetic resonance cholangiopancreatography, the recurrence rate appeared to be lower after cholecystectomy (4 of 36 (11 per cent) versus 42 of 108 (38·9 per cent); risk ratio 0·41, 0·16 to 1·07). Conclusion: Cholecystectomy after an episode of IAP reduces the risk of recurrent pancreatitis. This implies that current diagnostics are insufficient to exclude a biliary cause. Abstract : Idiopathic acute pancreatitis recurs more often than acute pancreatitis of known cause. In at least some of these patients, standard diagnostics (laboratory tests, transabdominal ultrasonography) may fail to detect biliary disease. The literature on cholecystectomy as a preventive measure for recurrence of pancreatitis in presumed idiopathic acute pancreatitis was reviewed systematically. Cholecystectomy can reduce pancreatitis Abstract : Antecedentes: Se ha sugerido que la enfermedad biliar oculta es una causa subyacente frecuente de pancreatitis aguda idiopática ( idiopathic acute pancreatitis, IAP). La colecistectomía se ha propuesto como una estrategia para prevenir la IAP recidivante. El objetivo de esta revisión sistemática era determinar la eficacia de la colecistectomía para reducir el riesgo de la IAP recidivante. Métodos: Se realizó una búsqueda sistemática en PubMed, Embase y Cochrane de estudios que incluían pacientes con IAP tratados con colecistectomía, y con datos sobre la recidiva de la pancreatitis. Se excluyeron los estudios anteriores a 1980, los que incluían pancreatitis crónica y los casos clínicos. El resultado principal fue la tasa de recidiva. La calidad se evaluó utilizando la escala de Newcastle‐Ottawa. Se realizaron metaanálisis para calcular la tasa de riesgo utilizando un modelo de efectos aleatorios con el método de varianza inversa. Resultados: En total, se incluyeron 10 estudios, de los cuales 9 se utilizaron para realizar análisis agrupados. La población de estudio incluyó 524 pacientes en los que se habían efectuado 126 colecistectomías. De estos 524 pacientes, 154 (29% (i.c. del 95% 25, 5‐33, 3)) presentaron recidiva de la enfermedad. La tasa de recidiva fue significativamente menor después de la colecistectomía que después del tratamiento conservador (14/126 (11%) versus 140/398 (35)); tasa de riesgo 0, 44 (i.c. del 95% 0, 27‐0, 71)). Incluso en pacientes en los que se diagnosticó IAP tras haber efectuado pruebas diagnósticas más extensas, incluyendo ultrasonografía endoscópica o colangiopancreatografía por resonancia magnética, la tasa de recidiva después de la colecistectomía era menor (4/36 (11%) versus 42/108 (39%); tasa de riesgo 0, 41 (i.c. del 95% 0, 16‐1, 07)). Conclusión: La práctica de una colecistectomía después de un episodio de IAP disminuye el riesgo de pancreatitis recidivante. Esto implica que los diagnósticos actuales son insuficientes para excluir una causa biliar (PROSPERO CRD42017055275).